Mina53 catalyzes arginine demethylation of p53 to promote tumor growth - Lixiao Zhou; Liyang Yu; Shushu Song; Yong Wang; Qiang Zhu; Meng Li; Yutong Sha; Liang Xu; Xin Shu; Qingqing Liao; Ting Wu; Bing Yang; et al. (Cell Reports, 2025)
Summary: Arginine methylation is a common post-translational modification that plays critical roles in many biological processes. However, the existence of arginine demethylases that remove the modification has not been fully established. Here, we report that Myc-induced nuclear antigen 53 (Mina53), a member of the jumonji C (JmjC) protein family, is an arginine demethylase. Mina53 catalyzes the removal of asymmetric dimethylation at arginine 337 of p53. Mina53-mediated demethylation reduces p53 stability and oligomerization and alters chromatin modifications at the gene promoter, thereby suppressing p53-mediated transcriptional activation and cell-cycle arrest. Mina53 represses p53-dependent tumor suppression both in mouse xenografts and spontaneous tumor models. Moreover, downregulation of p53-mediated gene expression is observed in several types of cancer with elevated expression of Mina53. Thus, our study reveals a regulatory mechanism of p53 homeostasis and activity and, more broadly, defines a paradigm for dynamic arginine methylation in controlling important biological functions.